Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/mnras/sty1672
|View full text |Cite
|
Sign up to set email alerts
|

The role of spiral arms in Milky Way star formation

Abstract: What role does Galactic structure play in star formation? We have used the Herschel Hi-GAL compact-clump catalogue to examine trends in evolutionary stage over large spatial scales in the inner Galaxy. We examine the relationship between the fraction of clumps with embedded star formation (the star-forming fraction, or SFF) and other measures of star-formation activity. Based on a positive correlation between SFF and evolutionary indicators such as the luminosity-to-mass ratio, we assert that the SFF principal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 82 publications
7
16
0
Order By: Relevance
“…It was noted in Roberts (1969) and Sormani et al (2017) that the gas may shock in front of or even behind the minimum of the potential well. A similar explanation for an observed offset between gas content and star formation tracers in the Milky Way is discussed in Ragan et al (2018) and the references therein in greater detail. The exact position of the shock strongly depends on the local parameters such as the sound speed.…”
Section: The Milky Way From An Outside Perspectivesupporting
confidence: 55%
“…It was noted in Roberts (1969) and Sormani et al (2017) that the gas may shock in front of or even behind the minimum of the potential well. A similar explanation for an observed offset between gas content and star formation tracers in the Milky Way is discussed in Ragan et al (2018) and the references therein in greater detail. The exact position of the shock strongly depends on the local parameters such as the sound speed.…”
Section: The Milky Way From An Outside Perspectivesupporting
confidence: 55%
“…10), we qualitatively observe that spiral arm features seem to be associated with 13 CO components with larger linewidths. In general, we can see increased median σ v values within Galactocentric distances 6 kpc; as already speculated in Riener et al (2020), these increasing σ v values towards the inner Galaxy could be due to the presence of the Galactic bar and the observed overdensity of star-forming regions (Anderson et al 2017;Ragan et al 2018), but could also partly result from our inability to correctly decompose strongly blended emission lines. We can further see an increase of the median σ v values with heliocentric distance; for emission lines with v LSR < 20 km s −1 this is partly due to our use of the size-linewidth prior (Sect.…”
Section: Face-on View Of the 13 Co Emissionsupporting
confidence: 77%
“…Urquhart et al 2018), recent studies have found no significant impact of Galactic structure on the clump or star formation efficiency of dense clumps (e.g. Moore et al 2012;Eden et al 2013Eden et al , 2015Ragan et al 2016Ragan et al , 2018, or the physical properties of filaments (Schisano et al 2020) and molecular clumps (Rigby et al 2019). However, the last study reported differences in the linewidths between clumps located in interarm and spiral arm structures.…”
Section: Introductionmentioning
confidence: 95%
“…Data is binned into equally populated bins, rather than equal sized ones. See Ragan et al (2018) for further details. Shaded regions denote those outside the survey area.…”
Section: Locations Of Star Formationmentioning
confidence: 99%